2013
DOI: 10.5114/aoms.2012.29217
|View full text |Cite
|
Sign up to set email alerts
|

­ A survey of patient behaviours and beliefs regarding antibiotic self-medication for respiratory tract infections in Poland

Abstract: IntroductionSelf-medication can contribute to the inappropriate use of antibiotics in respiratory tract infections (RTI). This phenomenon has not been well described, particularly in Poland. The aim of our study was to describe the prevalence of antibiotic self-medication for RTI, to explore factors influencing antibiotic use without prescription, and to determine the available sources of such antibiotics.Material and methodsA self-administered questionnaire completed by patients presenting to family medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 20 publications
4
45
1
5
Order By: Relevance
“…A study conducted in the Netherlands reported that approximately half of the respondents believed that antibiotics are effective for treatment of viral infections . Another study in Poland showed that inappropriate belief of effective antibiotic therapy for RTIs has led to self‐medication in patients . Furthermore, older parents with lower education level and also prior experience of receiving antibiotics, have higher expectation to receive antibiotics for their children .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the Netherlands reported that approximately half of the respondents believed that antibiotics are effective for treatment of viral infections . Another study in Poland showed that inappropriate belief of effective antibiotic therapy for RTIs has led to self‐medication in patients . Furthermore, older parents with lower education level and also prior experience of receiving antibiotics, have higher expectation to receive antibiotics for their children .…”
Section: Discussionmentioning
confidence: 99%
“…Respondents' levels of knowledge were classified into 3 categories, i.e. low (score 0-4), moderate (score 5-9), and high (score [10][11][12][13][14]. Before being used for the survey, the questionnaire had been pretested to 30 individuals whose characteristics were similar to the study population in order to verify the clarity of the language used and the questionnaire's structure.…”
Section: Methodsmentioning
confidence: 99%
“…5,6,8,13,14 Unfortunately, those data are still limited in Indonesia, and most of the studies were conducted in Java.…”
mentioning
confidence: 99%
“…Demand side plays an important role in antibiotics use. Specifically, beliefs and knowledge about antibiotics,behaviors (such as over‐the‐counter medication and self‐medication), patients' perceptions regarding patient‐doctor interaction, and patients' prior experience with antibiotics are possible demand‐side factors. In China, people can access antibiotics through a prescription by a physician, from pharmacies or drug stores, or through leftover stock from prior illnesses …”
Section: Introductionmentioning
confidence: 99%